Bullying in Banyuwangi's Schools: A Social Studies-Based Comparison between Urban and Suburban Educational Settings - Sukidin; Giyantoro, Eko (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
This study aims to compare bullying cases at SMPN 1 Giri and SMPN 1 Licin in Banyuwangi Regency with a focus on the type, frequency, and impact experienced by students. The method used is a qualitative approach with a case study design, which involves in-depth interviews, observation, and document analysis. The results showed significant differences in the forms of bullying experienced by students in the two schools. SMPN 1 Giri tended to experience higher verbal and social bullying, while SMPN 1 Licin was more exposed to physical bullying. The psychological impact experienced by student victims was also more severe at SMPN 1 Giri, indicating the need for more comprehensive interventions. This study recommends the development of a bullying prevention program that involves all stakeholders in the school to create a safer and more supportive learning environment for students.